Earnings Management and Measurement Error - Christian Hofmann (BuR - Business Research, 2008)
In this paper I consider the impact of a noisy indicator regarding a managers manipulative behavior on optimal effort incentives and the extent of earnings management. The analysis in this paper extends a twotask, single performance measure LEN model by including a binary random variable. I show that contracting on the noisy indicator variable is not always useful. More specifically, the principal uses the indicator variable to prevent earnings management only under conditions where manipulative behavior is not excessive. Thus, under conditions of excessive earnings management, accounting adjustments that yield a more congruent overall performance measure can be more effective than an appraisal of the existence of earnings management to mitigate the earnings management problem.
urn:nbn:de:0009-20-16509
Keywords: 650; accounting; Gewinnverwendung; Anreizvertrag; Prinzipal-Agent-Theorie; Performance-Messung; Operations Research